Model pembelajaran PJOK berbasis experiential learning untuk meningkatkan basic movement skills - Ulfah, Widati Amalin; Putranto, Dedy (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
The low mastery of Basic Movement Skills (BMS) among elementary school students remains a fundamental issue in Physical Education, Sports, and Health (PJOK) learning. Many instructional activities are still teacher-centered and provide limited opportunities for students to engage in direct learning experiences. This condition leads to suboptimal development of fundamental movement abilities, which should serve as the foundation for students’ competence in performing various physical activities. This study aims to develop an Experiential Learning–based PJOK instructional model to improve the Basic Movement Skills of elementary school students. The research employed the ADDIE development model, consisting of the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students at SD Negeri 15 Pangkalpinang. Data were collected through observations, interviews, questionnaires, expert validation, and BMS tests. Expert validation results indicated that the developed model was highly feasible, with an average validation score of 88.6%. Both limited and extensive trials demonstrated a significant increase in students’ BMS scores (p < 0.05) after the implementation of the learning model. These findings suggest that the Experiential Learning–based PJOK model is not only feasible but also effective in improving elementary students’ fundamental movement skills. In conclusion, the developed model serves as an innovative alternative for PJOK instruction that is more active, reflective, and grounded in meaningful student experiences